Research on the rational aggregation of a transport tractor - Kambarov Bakhtiyor; Kholikov Bakhtiyor; Khudaykuliyev Razhabbai; Lavrov Aleksandr (E3S Web of Conferences)
The results of studying the resistance to traction of a tractor train consisting of models Belarus 80.1 tractor and two 2PТС-4-793 trailers, and how this resistance depends on the number of trailers, the load weight Gt , and the speed of movement are specified in the article. Obtained figures indicate that, while the weight of each trailer n remains constant, the force in tractor’s attachment increases as number of trailers increases. Conversely, the resistance coefficient f of support surface's slope angle α and the rolling resistance of the wheels decreases. For investigating the force at tractor trains Рtf on soil and gravel roads, it is recommended to use the slope angle 6° of support surface and rolling resistance coefficient values for the specific surface types gravel - f =0.03 and asphalt - f =0.018. At a speed of 35 km/h, maximum traction resistance force for tractor train with total mass of 15720 kg and four trailers reached 2592 N. Usage degree of calculated traction force in Belarus 80.1 tractor and four-loaded trailers of 2PТС-4-793 type train was 17%.